A Study of Process Skills in Mathematics: Elementary School and Madrasah Ibtidaiyah - Husni Sabil; Asrial Asrial; Syahrial Syahrial; Rahmi Rahmi; Adriyan Ardi Rahman (Jurnal Ilmiah Sekolah Dasar, 2021)
MathematicsÂ is learning that uses many numbers, so that many students do not like mathematics. Other research also states that students find it difficult to learn mathematics. The purpose of this is to compare and relate the skills of elementary school students and Islamic school students to the material. This study uses quantitative methods with associative and comparative types. The population in this study were 36 students in each school. The research instrument for students' process skills between SD (Elementary School) and MI (Madrasah Ibtidaiyah) on mathematics lessons. This study tested the statistics after performing statistical tests and assumption tests in normality tests, homogeneity tests, and linearity tests. The study results are that the data of SD and MI students are said to be expected, and the data are homogeneous, and there is a linear relationship between SD and MI students. There is a process of student skills between students in SD (Elementary School) and MI (Masrasah Ibtidaiyah) in learning mathematics. The correlation test results for each school shows that student responses affect students' learning process skills.